Numerical Modeling of Horizontal Buoyant Jet Entering Shallow Water with a Crossflow - Ou, Ruoyao (Université d'Ottawa / University of Ottawa, 2020)
Numerical methods have been widely used for prediction in various complex physical problems such as industrial outfall discharges. The discharge of industrial effluent from the outfall systems can be divided into two categories on the basis of whether salinity or temperature is the inducement to the density difference. The salinity induced buoyant effluent, which is called negatively buoyant jet, has a density higher than the receiving water, thus tending to sink. The temperature induced jet, which is called positively buoyant jet, has a density lower than the receiving water, thus tending to rise. In the present work, the temperature induced horizontal buoyant jet entering shallow water with a uniform crossflow is investigated by numerical simulations using a modified solver in OpenFOAM (twoLiquidMixingFoam). Various turbulence models have been applied in the numerical model to evaluate the effectiveness of these models in predicting the jet behavior. These numerical results are compared with data obtained from a previous experimental study by Johnston et al. (1993). The simulations are run with a number of sets of crossflow-to-jet velocity ratios and densimetric Froude numbers in order to find out their influences on the jet behavior. Additionally, the bed attachment effect, which is one of the major features of the jet, is also investigated. In conclusion, it was found that the k-Equation LES turbulence model outperformed the other two models in terms of the consistency with the experimental data. Both employed RANS models (realizable 𝑘 − ε and SST 𝑘 − 𝜔 model) have weakness in predicting the bed attachment effect. However, they are still capable of predicting the general density distribution in flow field when the bed attachment effect is not present.
Keywords: CFD; OpenFOAM; RANS; LES